Efficacy of Ginkgo biloba on parameters in glaucoma: A systematic review. - Julia Prinz; Verena Prokosch; Xiaosha Wang; Yuan Feng; Peter Walter; Matthias Fuest; Filippo Migliorini (PLoS ONE)
Purpose This study aims to analyse the efficacy of GBE administration in patients with glaucoma and healthy volunteers. Methods This systematic review was performed according to the PRISMA 2020 guidelines. All clinical studies investigating the efficacy of GBE administration on the intraocular pressure (IOP), the corrected pattern standard deviation (CPSD) and the mean deviation of visual field testing, and heart rate were considered. The weighted mean difference (MD) effect measure, 95% confidence interval (CI), and t-test were used for continuous variables. Results Data from 8 studies, including 428 patients, were retrieved. The mean age of all patients was 51.1 ± 15.5 years. The median follow-up was 3.7 (IQR 9.4) months. The administration of GBE was not associated with an improvement in IOP (MD -1.5; 95%CI -7.1 to 9.6; P = 0.5), mean deviation (MD 0.7; 95%CI -9.4 to 8.2; P = 0.8), CPSD (MD -1.6; 95%CI -3.8 to 6.9; P = 0.5), or heart rate (MD -2.5; 95%CI -11.5 to 16.5; P = 0.4) from baseline to the last follow-up. There was no difference between GBE versus the control group in IOP (MD 1.1; 95%CI -5.7 to 3.5; P = 0.4), mean deviation (MD -0.4; 95%CI -9.1 to 9.9; P = 0.9), CPSD (MD 0.3; 95%CI -6.8 to 6.2; P = 0.9), and heart rate (MD -1.3; 95%CI -15.1 to 17.7; P = 0.8) at the last follow-up. Conclusion Currently, the evidence is not sufficient to conclude that GBE affects IOP, mean deviation, CPSD, or heart rate in glaucoma patients and healthy volunteers. These conclusions must be interpreted with caution given the limitations of the reviewed studies, particularly the follow-up time of the included studies.